Improving physical properties of degraded soil: Potential of poultry manure and biochar - Are, Kayode Steven; Adelana, Ayodele Olumide; Fademi, IbukunOluwa Oladapo; Aina, Oluseyi Abel (Agriculture and Natural Resources, 2017)
The application of organic materials for soil amendment plays important roles in reclaiming and improving the physical quality (SPQ) of degraded soils. This study assessed the effects of composted and non-composted poultry manures and biochar on the SPQ indicators of a degraded soil. A randomized complete block design was applied with four replications using five treatments: 1) veticompost (composted poultry manure + vetiver grass prunes), 2) poultry tea (non-composted poultry slurry), 3) solid non-composted poultry manure, 4) poultry biochar and 5) an unamended control. The soil physical quality indicators were determined after four consecutive growing seasons, with maize (Zea mays var. DMR-ESR-Y) planted as the test crop in each season. In comparison with the other treatments, poultry biochar consistently retained 3.3-31.3% more water at lower suctions (0-500 kPa). The saturated hydraulic conductivity following the application of poultry biochar (9.2 mm/hr) was significantly lower (p < 0.05) than for other organic amendments (16.5-18.2 mm/hr). The increase in water stable aggregates under the veticompost treatment was 3.4-26.7% greater than for the other treatments. The comparison of the SPQ indices indicated positive effects from the amendments on the soil physical properties in the order: unamended control < poultry biochar < poultry tea < non-composted poultry manure < veticompost. Composted and non-composted manures and biochar favored better maize growth and resulted in significantly higher grain yields (1.48-1.73 t/ha) than the unamended control treatments (0.87 t/ha). These results suggest that composted and non-composted manures may be more worthwhile than biochar for improving the physical quality of degraded soil.